Effects of monensin sodium and xylanase on growth performance of broiler chicks - Roskilly, Samantha D.; Delfelder, C.J.; Beyer, R. Scott; Stark, Charles R.; Evans, C.E.; Yoder, Ashton D.; Jones, Cassandra K. (My University, 2017)
There is an increasing consumer pressure to limit or eliminate antimicrobial usage in poultry feed. Antimicrobials have been used in poultry feed to improve nutrient digestibility to achieve a better feed to gain ratio. One alternative could be to replace antimicrobials with exogenous xylanase. Xylanase helps break down components of cell wall matrix of plants, which will improve digestibility in high fiber diets, however it is unknown if it can replace an antimicrobial, such as monensin sodium. This experiment was conducted to evaluate if xylanase can replace monensin sodium to improve nutrient digestibility, and if the amount of fiber impacts the amount of improvement in digestion. A total of 216 Cobb 1 day old chicks (6 birds/cage and 6 cages/treatment) were fed were fed one of six dietary treatments being corn or wheat-based diets supplemented with either 0.10 g/kg monensin sodium (Coban 90; Elanco Animal Health, Greenfield, IN) or 16,000 betaxlylanse units/kg beta 1-4, endo-xylanase enzyme (Econase XT; AB Vista, Marlborough, UK). The birds were housed in battery cages and were fed for 21 days’ ad libitum. Body weight and feed intake were recorded weekly to determine BW gain, total feed intake, and FCR. We had six diets that were fed as followed: 1) corn-based with no monensin sodium or xylanase; 2) wheat-based with no monensin sodium or xylanase; 3) corn-based with monensin sodium but no xylanse; 4) wheat-based with monensin sodium but no xylanase; 5) corn-based with xylanase but not monensin sodium; and 6) wheat-based with xylanase but no monensin sodium. Data was analyzed using the GLIMMIX procedure of SAS with cage as the experimental unit and treatment as the fixed effect. Treatment impacted (P < 0.01) final BW, feed intake, and FCR. The corn-based control diet had improved (P < 0.05) FCR compared to the wheat-based control diet. In corn-based diets, neither did monensin sodium or the xylanase had improvement (P > 0.05) FCR compared to the corn-based control. In wheat-based diets, xylanase (P < 0.05), but not monensin sodium showed no (P > 0.05) improved in FCR compared to the wheat-based control diet. In conclusion, this research suggests that xylanase helps improve the digestibility of carbohydrates in wheat- based diets, comparable to the digestibility corn based diets. However, there was a limited effect of feed an antimicrobial in the battery cage setting.
Keywords: Spring 2017